# |
ODE |
Mathematica |
Maple |
\[
{}y^{\prime } = -\cot \left (t \right ) y+6 \cos \left (t \right )^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }-x y^{3} = 0
\] |
✓ |
✓ |
|
\[
{}\frac {y^{\prime }}{\tan \left (x \right )}-\frac {y}{x^{2}+1} = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime }+x y^{2} = 4 y^{2}
\] |
✓ |
✓ |
|
\[
{}y \left (2 x^{2} y^{2}+1\right ) y^{\prime }+x \left (y^{4}+1\right ) = 0
\] |
✓ |
✓ |
|
\[
{}2 x y^{\prime }+3 x +y = 0
\] |
✓ |
✓ |
|
\[
{}\left (\cos \left (x \right )^{2}+y \sin \left (2 x \right )\right ) y^{\prime }+y^{2} = 0
\] |
✓ |
✓ |
|
\[
{}\left (-x^{2}+1\right ) y^{\prime }+4 x y = \left (-x^{2}+1\right )^{{3}/{2}}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }-y \cot \left (x \right )+\frac {1}{\sin \left (x \right )} = 0
\] |
✓ |
✓ |
|
\[
{}\left (y^{3}+x \right ) y^{\prime } = y
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = -\frac {2 x^{2}+y^{2}+x}{x y}
\] |
✓ |
✓ |
|
\[
{}\left (y-x \right ) y^{\prime }+2 x +3 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {1}{x +2 y+1}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = -\frac {x +y}{3 x +3 y-4}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \tan \left (x \right ) \cos \left (y\right ) \left (\cos \left (y\right )+\sin \left (y\right )\right )
\] |
✓ |
✓ |
|
\[
{}x \left (1-2 x^{2} y\right ) y^{\prime }+y = 3 x^{2} y^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+\frac {x y}{a^{2}+x^{2}} = x
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {4 y^{2}}{x^{2}}-y^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }-\frac {y}{x} = 1
\] |
✓ |
✓ |
|
\[
{}y^{\prime }-y \tan \left (x \right ) = 1
\] |
✓ |
✓ |
|
\[
{}y^{\prime }-\frac {y^{2}}{x^{2}} = {\frac {1}{4}}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }-\frac {y^{2}}{x^{2}} = {\frac {1}{4}}
\] |
✓ |
✓ |
|
\[
{}\sin \left (x \right ) y^{\prime }+2 y \cos \left (x \right ) = 1
\] |
✓ |
✓ |
|
\[
{}\left (5 x +y-7\right ) y^{\prime } = 3 x +3 y+3
\] |
✓ |
✓ |
|
\[
{}x y^{\prime }+y-\frac {y^{2}}{x^{{3}/{2}}} = 0
\] |
✓ |
✓ |
|
\[
{}\left (2 \sin \left (y\right )-x \right ) y^{\prime } = \tan \left (y\right )
\] |
✓ |
✓ |
|
\[
{}\left (2 \sin \left (y\right )-x \right ) y^{\prime } = \tan \left (y\right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = 2 x y
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {y^{2}}{x^{2}+1}
\] |
✓ |
✓ |
|
\[
{}{\mathrm e}^{x +y} y^{\prime }-1 = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {y}{x \ln \left (x \right )}
\] |
✓ |
✓ |
|
\[
{}y-\left (x -2\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {2 x \left (y-1\right )}{x^{2}+3}
\] |
✓ |
✓ |
|
\[
{}-x y^{\prime }+y = 3-2 x^{2} y^{\prime }
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {\cos \left (x -y\right )}{\sin \left (x \right ) \sin \left (y\right )}-1
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {x \left (y^{2}-1\right )}{2 \left (x -1\right ) \left (x -2\right )}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {x^{2} y-32}{-x^{2}+16}+32
\] |
✓ |
✓ |
|
\[
{}\left (x -a \right ) \left (x -b \right ) y^{\prime }-y+c = 0
\] |
✓ |
✓ |
|
\[
{}\left (x^{2}+1\right ) y^{\prime }+y^{2} = -1
\] |
✓ |
✓ |
|
\[
{}\left (-x^{2}+1\right ) y^{\prime }+x y = a x
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = 1-\frac {\sin \left (x +y\right )}{\sin \left (y\right ) \cos \left (x \right )}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = y^{3} \sin \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime }-y = {\mathrm e}^{2 x}
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime }-4 x y = x^{7} \sin \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+2 x y = 2 x^{3}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+\frac {2 x y}{x^{2}+1} = 4 x
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+\frac {2 x y}{x^{2}+1} = \frac {4}{\left (x^{2}+1\right )^{2}}
\] |
✓ |
✓ |
|
\[
{}2 \cos \left (x \right )^{2} y^{\prime }+y \sin \left (2 x \right ) = 4 \cos \left (x \right )^{4}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+\frac {y}{x \ln \left (x \right )} = 9 x^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }-y \tan \left (x \right ) = 8 \sin \left (x \right )^{3}
\] |
✓ |
✓ |
|
\[
{}t x^{\prime }+2 x = 4 \,{\mathrm e}^{t}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \sin \left (x \right ) \left (y \sec \left (x \right )-2\right )
\] |
✓ |
✓ |
|
\[
{}1-y \sin \left (x \right )-\cos \left (x \right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime }-\frac {y}{x} = 2 \ln \left (x \right ) x^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+\alpha y = {\mathrm e}^{\beta x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+\frac {m}{x} = \ln \left (x \right )
\] |
✓ |
✓ |
|
\[
{}\left (3 x -y\right ) y^{\prime } = 3 y
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {\left (x +y\right )^{2}}{2 x^{2}}
\] |
✓ |
✓ |
|
\[
{}\sin \left (\frac {y}{x}\right ) \left (x y^{\prime }-y\right ) = x \cos \left (\frac {y}{x}\right )
\] |
✓ |
✓ |
|
\[
{}x y^{\prime } = \sqrt {16 x^{2}-y^{2}}+y
\] |
✓ |
✓ |
|
\[
{}x y^{\prime }-y = \sqrt {9 x^{2}+y^{2}}
\] |
✓ |
✓ |
|
\[
{}x \left (x^{2}-y^{2}\right )-x \left (x^{2}+y^{2}\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}x y^{\prime }+y \ln \left (x \right ) = y \ln \left (y\right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {y^{2}+2 x y-2 x^{2}}{x^{2}-x y+y^{2}}
\] |
✓ |
✓ |
|
\[
{}2 x y y^{\prime }-x^{2} {\mathrm e}^{-\frac {y^{2}}{x^{2}}}-2 y^{2} = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime } = y^{2}+3 x y+x^{2}
\] |
✓ |
✓ |
|
\[
{}y y^{\prime } = -x +\sqrt {x^{2}+y^{2}}
\] |
✓ |
✓ |
|
\[
{}2 x \left (y+2 x \right ) y^{\prime } = \left (4 x -y\right ) y
\] |
✓ |
✓ |
|
\[
{}x y^{\prime } = x \tan \left (\frac {y}{x}\right )+y
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {x \sqrt {x^{2}+y^{2}}+y^{2}}{x y}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = -y^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {y}{2 x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {{\mathrm e}^{x}-\sin \left (y\right )}{x \cos \left (y\right )}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {1-y^{2}}{2 x y+2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {\left (1-y \,{\mathrm e}^{x y}\right ) {\mathrm e}^{-x y}}{x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {x^{2} \left (1-y^{2}\right )+y \,{\mathrm e}^{\frac {y}{x}}}{x \left ({\mathrm e}^{\frac {y}{x}}+2 x^{2} y\right )}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {\cos \left (x \right )-2 x y^{2}}{2 x^{2} y}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \sin \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {1}{x^{{2}/{3}}}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \ln \left (x \right ) x^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = 2 x y
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {y^{2}}{x^{2}+1}
\] |
✓ |
✓ |
|
\[
{}{\mathrm e}^{x +y} y^{\prime }-1 = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {y}{x \ln \left (x \right )}
\] |
✓ |
✓ |
|
\[
{}y-\left (x -1\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {2 x \left (y-1\right )}{x^{2}+3}
\] |
✓ |
✓ |
|
\[
{}-x y^{\prime }+y = 3-2 x^{2} y^{\prime }
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {\cos \left (x -y\right )}{\sin \left (x \right ) \sin \left (y\right )}-1
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {x \left (y^{2}-1\right )}{2 \left (x -1\right ) \left (x -2\right )}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {x^{2} y-32}{-x^{2}+16}+2
\] |
✓ |
✓ |
|
\[
{}\left (x -a \right ) \left (x -b \right ) y^{\prime }-y+c = 0
\] |
✓ |
✓ |
|
\[
{}\left (x^{2}+1\right ) y^{\prime }+y^{2} = -1
\] |
✓ |
✓ |
|
\[
{}\left (-x^{2}+1\right ) y^{\prime }+x y = a x
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = 1-\frac {\sin \left (x +y\right )}{\sin \left (y\right ) \cos \left (x \right )}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = y^{3} \sin \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {2 \sqrt {y-1}}{3}
\] |
✓ |
✓ |
|
\[
{}m v^{\prime } = m g -k v^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+y = 4 \,{\mathrm e}^{x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+\frac {2 y}{x} = 5 x^{2}
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime }-4 x y = x^{7} \sin \left (x \right )
\] |
✓ |
✓ |
|